A expressão de fosfodiesterases da família 4A em adenomas hipofisários esporádicos e em adenomas hipofisários com diferentes mutações do gene que codifica a proteína de interação com o receptor Aril hidrocarbono (AIP) - Mariana Ferreira Bizzi (2015)
Human phosphodiesterases (PDEs) comprise a complex superfamily of enzymes derived from 21 genes separated into 11 PDE gene families (PDEs 1-11), diffused in different tissues and cells, including heart and brain. The isoforms PDE 4, 7 and 8 are specific for cAMP. This second messenger is responsible for mediating diverse physiological actions involving different hormones and neurotransmitters. The cAMP pathway play an important role in development and function of endocrine tissues. Already phosphodiesterases are responsible for ensuring the appropriate intensity of the actions of this pathway, as they are enzymes responsible for hydrolysis of cAMP in its inactive form 5'-AMP. The objective of this work is to study the expression of phosphodiesterase 4A family in sporadic pituitary adenomas and pituitary adenomas with different mutations of the gene encoding the aryl hydrocarbon receptor interacting protein (AIP). Paraffin sections samples obtained by pituitary adenomas biopsies without mutation the AIP, representing each of the principal subtypes of adenomas: GH-secreting tumour; PRL-secreting tumour; ACTH-secreting tumour and non-functioning pituitary tumour positive for FSH (NFPAs) were included in the study. Also included samples of GH-secreting tumours with AIP mutation (Q164X, INS274, R304X, R304Q, Glu2228, Unusual) and normal pituitary. The samples were subjected to the double immunofluorescent staining for co-location PDE4A in different cell types of pituitary. The analysis were in confocal microscopy and the images analyzed by ImageJ software. Both PDE4A isoforms analyzed in this study are present in different cellular types of human pituitary. The expression pattern of these PDEs varied according to cell type. PDE4A4 expression was higher in GH and FSH normal pituitary cells while for PDE4A8, the expression was higher in the normal PRL, GH and FSH pituitary cells. However, indepedent of the isoform of PDE4A, the expression is increased in all sporadic pituitary adenomas (P <0.0001). In the GH-secreting tumors with AIP mutation the expression of PDEs varies depending upon the mutation. These data suggest for the first time that both isoforms presented in this study are expressed in the tissue from human normal pituitary; the increased expression of PDEs in sporadic pituitary adenomas may be a compensatory response to tumorigenesis; and PDEs expression in pituitary tumors is interrupted by several AIP mutations, suggesting a putative role of this isoform in pituitary tumorigenesis, and possibly contributing to the loss of AIP function.